Soviet Union, but Without the USSR - Lisitsina, Yana (project baikal, 2019)
The article raises the question of the formation of a professional creative organization – the Union of Soviet Artists, initiated by the resolution of the Central Committee of the CPSU(b) of 23.04.1932. On the basis of archival documents the article considers the initial stage of the Union of Artists of the East Siberian region – VSKRASSKh.